Surgical approaches for minimally invasive plate osteosynthesis in dogs - Pozzi, A.; Lewis, D. D. (Veterinary and Comparative Orthopaedics and Traumatology, 2009)
Fracture stabilisation techniques continue to evolve and to provide approaches which minimise the iatrogenic trauma associated with surgery. Minimally invasive plate osteo-synthesis (MIPO) is a recently described method of biological internal fixation performed by introducing a bone plate via small insertional incisions that are made remote to the fracture site. The plate is slid adjacent to the bone in an epiperiosteal tunnel connecting the two insertional incisions. Screws are placed in the plate through the insertional incisions or via additional stab incisions made over the holes in the plate. In this paper we describe the surgical approaches used to perform MIPO in humeral, radial, fe-moral and tibial fractures in dogs. We found that these approaches allowed safe insertion of the plate without grossly damaging neuro-vascular structures. Further studies are needed to evaluate the clinical outcome of MIPO in dogs.
Keywords: Dog; plate; approach; fracture; MIPO